Pengaruh Total Aset, Jumlah Simpanan dan Jumlah Anggota terhadap Sisa Hasil Usaha pada Koperasi Pegawai Republik Indonesia PGRI Sejahtera Lestari Kecamatan Batang Cenaku - Gita Sari Gustika; Yenny Iskandar; Silviayan Arnindhita (Universitas Batanghari, 2022)
The remaining operating results of the Indonesian Civil Servant Cooperative PGRI Sejahtera Lestari, Batang Cenaku Subdistrict, fluctuated, meaning that there was an increase and a decrease. This increase and decrease is influenced by total assets, total deposits, and number of members. Total assets, total deposits, and number of members also fluctuated. This research was conducted at the Indonesian Civil Servant Cooperative PGRI Sejahtera Lestari, Batang Cenaku District. The purpose of this research is to analyze the total assets, the number of deposits, and the number of members that affect the remaining operating results of the Indonesian Employee Cooperative PGRI Sejahtera Lestari, Batang Cenaku District. Cenaku To analyze the amount of savings that affect the remaining operating results of the Indonesian Employee Cooperative PGRI Sejahtera Lestari Batang Cenaku District. This type of research is quantitative. The data used is secondary data. With data collection techniques using literature study techniques, documentation studies, and interviews. The method used to analyze the data is quantitative method, namely multiple linear regression analysis, correlation coefficient and determination, F test and t test. Based on the results of research and discussion, some conclusions can be drawn as follows: Total assets, total savings, and number of members simultaneously have no significant effect on the remaining operating results of the Indonesian Employee Cooperative PGRI Sejahtera Lestari, Batang Cenaku District. Total assets partially have no significant effect on variable residual operating results in the Employee Cooperative of the Republic of Indonesia PGRI Sejahtera Lestari, Batang Cenaku Subdistrict The number of deposits partially has no significant effect on the variable remaining operating results in the Republic of Indonesia Employee Cooperative PGRI Sejahtera Lestari, Batang Cenaku Subdistrict. Indonesian Civil Servants Cooperative PGRI Sejahtera Lestari, Batang Cenaku Distri.